British Crime Survey, 1982 ([Verlag nicht ermittelbar], 1987)
The primary purpose of the British Crime Survey was to estimate how many of the public in England and Wales are victims of selected types of crime over a year, describing the circumstances under which people become victims, and the consequences of crime for victims. Other aims included providing background information on fear of crime among the public and on public contact with the police. Respondents were asked a series of screening questions to establish whether or not they or their households had been victims of relevant crimes during the one-year reference period. They were then asked a series of very detailed questions about the incidents they reported. Basic descriptive background information on respondents and their households was collected to allow analysis of the sorts of people who do and do not become victims. Information was also collected on other areas which were of intrinsic interest and which could usefully be related to experience as a victim, namely, fear of crime, contact with the police, lifestyle, and self-reported offending.